The Signs and Symbols in Christropher’s Way of Thinking in the Curious Incident of the Dog in the Night-Time - FEBRIAN EKA ADITYA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Studi ini membahas refleksi dari tanda-tanda dan simbol dalam cara berpikir anak autis diwakili oleh Christopher John Francis Boone sebagai karakter utama dalam novel The Cuirous Incident of The Dog in The Night-Time oleh Mark Haddon. Untuk melakukan analisis, dua teori diterapkan; teori semiotika dan teori tanda-tanda dan simbol. Ada dua masalah akan dijawab dengan menggunakan teori-teori tersebut. Masalah pertama adalah apa tanda-tanda dan simbol-simbol yang digunakan dalam cara berpikir Christopher dalam novel. Masalah ini akan dijawab oleh teori tanda dan symbol yang telah dirumuskan oleh Ferdinand de Saussure. Masalah kedua adalah maksud tanda dan symbol dalam cara berpikir Christopher, pertanyaan ini juga dapat dianalisis dengan teori semiotika yang dirumuskan oleh Ferdinand de Saussure. Mengungkap tanda-tanda dan simbol adalah untuk memberikan refleksi bagaimana cara Christopher berpikir sebagai karakter utama dalam novel. Hasil dari diskusi ini menghasilkan arti dari tanda-tanda dan simbol-simbol yang terungkap dalam cara berpikir Christopher. Kata Kunci: Semiotika, Tanda-tanda, Simbol, Karakter Utama Abstract This study discusses in The Curious Incident of the Dog in the Night-Time written by Mark Haddon the reflections of Signs and Symbols in the way of thinking of an autistic child represented by Christopher John Francis Boone as the main character. To do the analysis, two theories are applied; they are theory of semiotics and theory of signs and symbols. There are two problems will be answered by using those theories. The first problem is what are signs and symbols used in Christopher’s way of thinking in The Curious Incident of the Dog in the Night-Time. This problem will be answered by the theory of signs and symbols that has been specialized and brought by Ferdinand de Saussure. The second problem is what the signs and symbols mean in Christopher’s way of thinking as the second questions will also be analyzed with the theory of semiotics brought by Ferdinand de Saussure. The revealing of signs and symbols is to give description of how Christopher thinks as the representative main character in the novel. The outcomes of discussion represent what the signs and symbols that revealed can be meant in Christopher’s way of thinking. Keywords: Semiotics, Signs, Symbols, Main Character